The midwife [videorecording (DVD)] - Provost, Martin; Provost, Martin; Deneuve, Catherine, 1943-; Frot, Catherine, 1956-; Gourmet, Olivier (Music Box Films, 2017)
An unlikely friendship develops between Claire, a devout and compassionate midwife, and Béatrice, her father's mistress, who unexpectedly shows up after thirty years of absence and reveals that she has a brain cancer.